2018
DOI: 10.1002/berj.3332
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of home and preschool learning environments on early language development

Abstract: The present study is based on longitudinal data from a German early childhood education and care (ECEC) governmental initiative assessing children's grammatical and vocabulary development between 2;6 and 4;0 years (N = 1,331), quality of the home learning environment and quality of the preschool setting. Results showed that the quality of the home learning environment predicted development in grammatical skills, but not in receptive vocabulary at age 4, while the effects of preschool process quality showed sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 38 publications
1
18
0
1
Order By: Relevance
“…Thus, children’s milestone development can to a high degree be assumed to be shaped by their learning environment. According to studies of language attainment, the quality of this learning environment has especially been investigated in the home [3335], and the results emphasize quality of the parent-child interaction [34, 35], maternal responsiveness [36, 37], and appropriate play materials as important predictors [34, 35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, children’s milestone development can to a high degree be assumed to be shaped by their learning environment. According to studies of language attainment, the quality of this learning environment has especially been investigated in the home [3335], and the results emphasize quality of the parent-child interaction [34, 35], maternal responsiveness [36, 37], and appropriate play materials as important predictors [34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…However, early developmental factors such as gestational age [2729] and low birth weight [3032] have also been found to be associated with later attainment of language milestones. For postnatal factors, focus has especially been on parental factors, including the home environment [3335] and emphasizes maternal responsiveness [36, 37] as an important predictor of language development. Finally, there have been studies of developmental continuity showing that the timing of earlier motor developmental milestones may be a good predictor of the attainment of language milestones [3, 38].…”
Section: Introductionmentioning
confidence: 99%
“…On the microsystem level, educational research has identified two environments that are related to children’s oral language development through shared reading: the HLE and the CCLE ( Sénéchal et al, 1996 ; Weigel et al, 2005 ; Ebert et al, 2013 ; Niklas and Schneider, 2013 ; Weinert and Ebert, 2013 ). Some studies found that the HLE is more closely related to oral language than the CCLE ( Ebert et al, 2013 ; Weinert and Ebert, 2013 ; Grolig et al, 2019 ), whereas other studies found that the influence of both literacy environments had a similar magnitude ( Weigel et al, 2005 ; Schmerse et al, 2018 ).…”
Section: Environments and Language Developmentmentioning
confidence: 99%
“…A crucial issue in this regard is whether potential preschool quality effects on learning‐related behaviors are more important to children from disadvantaged socioeconomic backgrounds. Although a large body of research has documented the developmental importance of early teacher–child interactions for school readiness skills, it remains a topic of intense debate if the quality of early education is related to developmental outcomes differently for children with socioeconomic risk factors (e.g., Dearing, McCartney, & Taylor, 2009; Keys et al, 2013; Schmerse et al, 2018; Votruba‐Drzal, Coley, & Chase‐Lansdale, 2004). Thus far, research has examined differential effects of preschool quality for various outcomes including academic skills, social skills, and problem behaviors.…”
Section: Learning‐related Behavior and Academic Achievementmentioning
confidence: 99%
“…However, evidence that effects of higher preschool quality vary by academic or socioeconomic risk factors is mixed in the literature. While some studies (e.g., Dearing et al, 2009; Votruba‐Drzal et al, 2004) demonstrate compensatory effects, others have found that children from more advantaged home leaning environments profited more from high preschool quality (e.g., Anders et al, 2012; Schmerse et al, 2018). Recent meta‐analytic research on longitudinal correlational data revealed limited evidence to support the hypothesis that effects of preschool quality are moderated by children’s entry‐level skills or socioeconomic family characteristics (Keys et al, 2013).…”
Section: Learning‐related Behavior and Academic Achievementmentioning
confidence: 99%